"I can't believe your mixed ass wasn't on the pill!": race and abortion on American scripted television, 2008-2019. Issue 4 (19th May 2022) - Herold, Stephanie; Sisson, Gretchen; Bracey Sherman, Renee
ABSTRACT: Racial identities provide important context for understanding reproductive experiences, including abortion. However, this context is often not fully reflected in popular cultural narratives about abortion, including on American television. Because onscreen depictions have the potential to influence public understandings of abortion, it is crucial to examine the messages these plotlines convey about the relationship between race, racism, and abortion access. We analyze a decade of onscreen abortion depictions, finding that the vast majority contain no racially-specific content. When plotlines do portray a character of color obtaining an abortion, these depictions can be both progressive in making race visible and regressive in relying on problematic racial tropes. These patterns differed by race: Black characters often obtain abortions while wrestling with and reinforcing racial stereotypes; Latina characters' abortion stories are predominantly concerned with Catholic judgment. Plotlines featuring Asian or multiracial characters are largely absent. In contrast, white characters' stories comprise the vast majority of abortions on television, and none of these plotlines substantially address issues of race. These disparate patterns obfuscate structural barriers to abortion access and may contribute to the skewed beliefs that the American public holds about abortion.